The effect of calcitriol on the development and implantation capacity of embryos from hyper-stimulated mice - Bognár, Zoltán; Csabai- Tanics, Timea Judith; Görgey, Éva; Mikó, Éva; Horváth-Szalai, Zoltán; Szekeres-Barthó, Júlia (Frontiers in Immunology, 2023)
The evidence concerning the role of vitamin D (VD) in reproduction is still inconclusive. Calcitriol was given to superovulated female mice at the time of FSH injection (Group A), or at day 0.5 of pregnancy (Group B). The retrieved and cultured embryos were transferred to the uteri of pseudopregnant females. Ten animals from each group conceived naturally, and at day 7.5 of pregnancy, the implantation sites were counted. Serum hormone concentrations were determined by ELISA. The expression of CD70, PD-L1, OX-40L, and PIBF on extracellular vesicles (EVs) was tested by flow cytometry.Calcitriol treatment did not alter serum oestradiol concentrations, while 25(OH) D levels significantly decreased in both treated groups. Progesterone concentrations were significantly higher in group A and lower in group B than in the controls.On EVs produced by group B embryos PIBF, CD70, and OX-40L expression were significantly lower, while that of PD-L1 was significantly higher than that of controls.Calcitriol treatment decreased the fertilization rate in group A, and the blastulation rate of cultured embryos in group B, while the implantation capacity of the embryos was not affected, suggesting that depending on the time of administration, VD has an adverse effect on oocyte maturation and embryo development, but not on the implantation rates.